Case Study: The Exercise Profile of a Polish Representative in Mountain Running - Zbigniew Borysiuk; Katarzyna Piechota (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
This study is aimed at analysing the variability of oxygen parameters in subsequent annual training cycles at championship training level in mountain running. The study employed the following indirect methods: the Astrand Test, Conconi Running Test, and also a direct method (Bruce Test).
Research material is a young, talented 28-year-old athletic mountain runner. Research results were obtained within 4-5 years period, which were as follows: VO2max 83-90ml/kg/min - increased on average to 2-3 ml / kg / min per year, HR max 172-177 beats / min, PPA 158-169 beats / min. The case study was carried out within the framework of longitudinal research and was used to collect data for the formulation of a specific exercise profile in a new, dynamic sports discipline.
The research aims to serve as an example of a novel method of conducting training microcycles to the cyclic lifting aerobic capacity athletes.